Measurement of Noradrenaline and Serotonin Metabolites With Internal Jugular Vein Sampling: An Indicator of Brain Monoamine Turnover in Depressive Illness and Panic Disorder - Esler, Murray; Alvarenga, Marlies; Barton, David; Jennings, Garry; Kaye, David; Guo, Ling; Schwarz, Rosemary; Lambert, Gavin (Frontiers in Psychiatry, 2022)
In research spanning three decades we have estimated brain monoamine turnover (approximately equating with synthesis rate) with sampling from the internal jugular veins and measurement of trans-cerebral plasma monoamine metabolite concentration gradients. Here we report indices of brain noradrenaline and serotonin turnover in patients with major depressive illness (MDD) and panic disorder (PD). Brain noradrenaline turnover was assessed from the combined flux into the internal jugular veins of the metabolites dihydroxyphenylglycol (DHPG) and 3-hydroxy-4-methoxyphenylglycol (MHPG), and brain serotonin turnover from the overflow of the primary metabolite, 5-hydroxyindole acetic acid (5HIAA). Comparison was made with matched healthy research participants. In both MD and PD the estimate of brain noradrenaline turnover provided by metabolite overflow was unremarkable. In contrast, in both patient groups the estimate of brain serotonin turnover provided by 5HIAA overflow was increased 3–4-fold (P < 0.01). This neurotransmitter abnormality was normalized in MDD and PD in clinical remission, during selective serotonin reuptake blocker (SSRI) dosing. We cannot be sure if the brain serotonergic abnormality we find in MDD and PD is causal or a correlate. Measurements in PD were not made during a panic attack. The increased estimated serotonin turnover here may possibly be a substrate for panic attacks; serotonergic raphe nuclei participate in anxiety responses in experimental animals. It is puzzling that the findings were identical in MDD and PD, although it may be pertinent that these psychiatric diagnoses are commonly comorbid. It is unlikely that activation of brain serotonergic neurons is driving the sympathetic nervous activation present, which contributes to cardiovascular risk, persistent sympathetic activation in MDD and episodic activation in PD during panic attacks. We have previously demonstrated that the mechanism of activation of human central sympathetic outflow in other contexts (hypertension, heart failure) is activation of noradrenergic brainstem neurons projecting to the hypothalamus and amygdala.